Réponses

2014-02-08T14:09:38+01:00
Trop simple
ex1) a)(5x-2)²=5x²+2²-2fois 5xfois2
         =5x²+4-20x
b)3x²+5/2²

exaille de faire lke 2 cest des identité remarquable

Meilleure réponse !
  • Omnes
  • Modérateur confirmé
2014-02-08T14:27:25+01:00
Salut,

exercice 1:

A = (5x-2)^{2} = (5x)^{2} - 2 * 2 * 5x + 2^{2} = 25x^{2} - 20x + 4\\
B = (3x +  \frac{5}{2}) (3x -  \frac{5}{2}) = (3x)^{2} - (\frac{5}{2})^{2} = 9 x^{2} -  \frac{25}{4}

Exercice 2:

A = ( \sqrt{2} -1)^{2} =  \sqrt{2}^{2}  - 2 *\sqrt{2} * 1 + 1^{2} = 2 - 2 \sqrt{2}   + 1 = 3 - 2 \sqrt{2} \\
B = ( \sqrt{3} - 2 )(\sqrt{3} + 2) =  \sqrt{3}^{2} - 2^{2} = 3 - 4 = -1 \\
C = (2 \sqrt{3}  + 3 )^{2} =  (2\sqrt{3})^{2} + 2 * 2\sqrt{3} * 3 + 3^{2} = 4*3 + 12\sqrt{3} + 9 \\
C = 12 + 9 + 12\sqrt{3} = 21 + 12\sqrt{3}

Exercice 3:
a)
X =
( \sqrt{3} +1)^{2} +  ( \sqrt{3} -1)^{2}= \sqrt{3}^{2} + 2 * \sqrt{3} *1 + 1 + \sqrt{3}^{2} - 2 * \sqrt{3}  * 1 + 1^{2} \\

X = 3 + 2 \sqrt{3} +1 + 3 - 2 \sqrt{3}  + 1 \\
X = 3 + 3 + 2   = 8\\

Y = ( \sqrt{3} +1)^{2} - ( \sqrt{3} -1)^{2} \\
Y = \sqrt{3}^{2} + 2 * \sqrt{3} *1 + 1^{2}  - (\sqrt{3}^{2} - 2 * \sqrt{3}  * 1 + 1^{2} )\\
Y = 3 + 2  \sqrt{3} + 1  - ( 3 -   2 \sqrt{3} +1) \\
Y = 3 + 2\sqrt{3}  + 1 - 3 +  2\sqrt{3} -1 \\
Y = 3 + 1 - 3 - 1 + 2\sqrt{3}+ 2\sqrt{3} \\
Y = 4\sqrt{3}

b) X est un entier, tandis que Y n'en est pas un (présence de la racine)
Bonne journée !